"Getting Under the Hood" of Neuronal Signaling in Caenorhabditis elegans. (15th June 2018) - Williams, Paul DE; Zahratka, Jeffrey A; Bamber, Bruce A
Caenorhabditis elegans is a powerful model to study the neural and biochemical basis of behavior. It combines a small, completely mapped nervous system, powerful genetic tools, and a transparent cuticle, allowing Ca ++ imaging without the need for dissection. However, these approaches remain one step removed from direct pharmacological and physiological characterization of individual neurons. Much can still be learned by "getting under the hood" or breaching the cuticle and directly studying the neurons. For example, we recently combined electrophysiology, Ca ++ imaging, and pharmacological analysis on partially dissected ASH nociceptors showing that serotonin (5-HT) potentiates depolarization by inhibiting Ca ++ influx. This study challenges the tacit assumption that Ca ++ transient amplitudes and depolarization strength are positively correlated and has validated a new paradigm for interpreting Ca ++ signals. Bypassing the cuticle was critical for the success of these experiments, not only for performing electrical recordings but also for the acute and reversible application of drugs. By contrast, drug soaking or mutating genes can produce long-term effects and compensatory changes, potentially confounding interpretations significantly. Therefore, direct studies of the physiological response of individual neurons should remain a critical objective, to provide key molecular insights complementing global Ca ++ imaging neural network studies.